Effect of Cryptolaemus montrouzieri (Coleoptera: Coccinellidae) in the parasitoid activity of Anagyrus kamali (Hymenoptera: Encyrtidae) on Maconellicoccus hirsutus (Hemiptera: Pseudococcidae) - HERNÁNDEZ-MORENO, SALVADOR; GONZÁLEZ-HERNÁNDEZ, HÉCTOR; LOMELI-FLORES, J. REFUGIO; RODRÍGUEZ-LEYVA, ESTEBAN; ROBLES-BERMÚDEZ, AGUSTÍN (Revista Colombiana de Entomología, 2012)
In several countries, Anagyrus kamali and Cryptolaemus montrouzieri have been introduced for the biological control of the pink hibiscus mealybug (PHM) Maconellicoccus hirsutus, but there is not a formal study to assess the interaction between those natural enemies. In the present study we evaluated, under laboratory conditions, the in teraction of C. montrouzieri (forthinstar larvae and adult female) in A. kamali parasitoid activity on PHM. Individual and simultaneous liberations of both species, using choice and nochoice tests, were made in order to determine the interaction between the predator and the parasitoid. Third PHM nymphs parasitized by A. kamali at different parasitoid maturation periods (egg, young larvae, mature larvae, young pupae and mature pupae) were used as hosts. The results showed that C. montrouzieri reduced the parasitoid activity of A. kamali to 2.2 and 5%. In the choice test, C. montrouz ieri did not discriminate against wealthy PHM and parasitoized under five days. In the nochoice tests, C. montrouzieri adults and larvae reduced their predatory activity when parasitized PHM had more than six days of having been parasit ized, possibly due to the hardening of PHM mummies. The results of the present study support the hypothesis that in the interaction between C. montrouzieri and A. kamali there is an antagonistic effect since the presence of the predator reduced the parasitic activity of A. kamali in the PHM control.